Soils in Understanding Land Surface Construction: An Example from Campania Plain, Southern Italy - Antonella Ermice; Rossana Marzaioli; Marco Vigliotti; Pierferdinando Lamberti; Daniela Ruberti (Quaternary)
The contribution of sediment transport and accumulation to soil formation was investigated in an area characterized by continental sedimentary activity since the Late Pleistocene. The area was the north-eastern portion of the large Quaternary graben represented by the Campania Plain, which is rimmed to the north–east–south by the Mesozoic carbonate Apennine nappes. The plain was filled mainly by products generated by eruptions from the Phlegrean Fields, which were also distributed on the slopes bordering the plain and remobilized toward the adjacent surfaces. Five sites were selected in the area in question. They were studied using morphological features and pertinent characteristics of the mineral soil fraction >2.0 mm, such as their volume and lithological description. Soils were compared to selected lithostratigraphic sequences characterizing the studied area, which were collected from literature and reinterpreted in pedological keys. The results showed that soils derived from the emplacement of Phlegrean primary volcanic materials, such as Campania Ignimbrite (~39–40 ky B.P.) and Neapolitan Yellow Tuff (~15 ky B.P.), with the related weathering products, and from volcanic materials reworked and transported by alluvial/colluvial episodes. The latter formed contrasting soil horizons which, differing in both rock fragment content and lithological composition, testified to the presence of lithological discontinuities. The formation of the horizons in question interrupted the genetic sequence derived from the in situ alteration of the volcanic substrata, suggesting that processes of transport and redistribution of sediments from the adjacent mountain slopes contributed to soil formation. The comparison of the pedostratigraphies with the lithostratigraphic sequences indicated a strong relation between geomorphic and pedogenetic events.